Prediction of the mesio-distal crown widths of unerupted cuspids and bicuspids in the Singapore Malay population. Issue 3 (1st September 2017) - Lu, Wilson; Wong, Hung Chew; Takada, Kenji
Abstract: Objective: (1) To develop models to predict the mesio-distal crown widths of the unerupted cuspids and bicuspids in the mixed-dentitions in the Singapore Malay population. (2) To evaluate the prediction accuracy of the proposed models. Materials and Methods: Dental cast records were obtained from 150 Singapore Malay orthodontic patients (70 males, mean 22.9 years; 80 females, mean 21.4 years). Mesio-distal crown widths, molar basal arch-lengths and intermolar distances were measured in the permanent maxillary and mandibular dentitions on the dental casts with a digital caliper. Regression equations for estimating the sum of the crown widths of the unerupted cuspids and bicuspids were determined using a stepwise multiple regression analysis and tested for validity. Estimations within 1.5 mm in the dental arch were deemed clinically acceptable and might not affect the decision of orthodontic tooth extraction or non-extraction in a permanent dentition as it may be compensated for by interproximal enameloplasty. As such, the prediction accuracy was defined as the percentage of the estimations falling within 1.5 mm of the actual summed widths of the cuspids and bicuspids within the dental arch and was derived using the validation dataset. Results: For the male subjects, the maxillary equation of Ŷ = 8.445 + 0.716 × U2 + 0.870 × U6 had a R 2 of 0.49 and the mandibular equation of Ŷ = 4.161 + 1.173 × L2 + 0.996 × L6 had a R 2 of 0.63. For the female subjects, the maxillary equation of Ŷ = 8.826 + 0.540 × U2 + 0.607 × U6 + 0.073 × UIMD had a R 2 of 0.42 and the mandibular equation of Ŷ = 9.815 + 1.005 × L1 + 1.081 × L2 had a R 2 of 0.44. Ŷ represents the estimated sum of the mesio-distal crown widths of the unerupted cuspids and bicuspids. The prediction models had accuracies of 90–100%. Conclusion: The proposed models were found to be effective for clinical use for the Singapore Malay orthodontic patients in the mixed-dentition.